A rare case of primary cutaneous B-Cell lymphoma in a child - J P Prathibha; Akanksha Prasad Cherala; Ishwara Bhat; Suravi Mohanthy (Wolters Kluwer Medknow Publications, 2023)
Primary cutaneous lymphomas (PCLs) are non-Hodgkin's lymphomas present in the skin, with no evidence of extracutaneous disease at the time of diagnosis. PCL is uncommon in children, and those that do exist are mostly of the T-cell lineage. PCL of the B-cell linage is most common in the sixth decade of life and is extremely rare in childhood.